2023
DOI: 10.3389/fpls.2023.1203881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physiological integration on nitrogen use efficiency of moso bamboo in homogeneous and heterogeneous environments

Abstract: IntroductionMoso bamboo is one of the important clonal plants with complex underground rhizome-root system. Ramets connected by rhizome can translocate and share nitrogen (N), which may affect the nitrogen use efficiency (NUE) of moso bamboo. The aims of this study were to investigate the mechanisms of N physiological integration and its relationship with NUE of moso bamboo.MethodsA pot experiment was conducted to trace the movement of 15N between the connected ramets of moso bamboo in both homogeneous and het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Therefore, achieving sustainable high yields in bamboo forests requires nutrient supplementation through fertilization. Among these, nitrogen fertilizer stands as the primary nutrient factor enhancing bamboo forest productivity ( Sardar et al., 2023 ; Zhao and Cai, 2023 ; Zou et al., 2023 ). In bamboo forest ecosystems, nitrogen allocation directly influences the growth of bamboo shoots, the development of bamboo culms, and the overall productivity of the stand ( Wu et al., 2023a ; Zuo et al., 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, achieving sustainable high yields in bamboo forests requires nutrient supplementation through fertilization. Among these, nitrogen fertilizer stands as the primary nutrient factor enhancing bamboo forest productivity ( Sardar et al., 2023 ; Zhao and Cai, 2023 ; Zou et al., 2023 ). In bamboo forest ecosystems, nitrogen allocation directly influences the growth of bamboo shoots, the development of bamboo culms, and the overall productivity of the stand ( Wu et al., 2023a ; Zuo et al., 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al found that the new shoots were more abundant in unfertilised plots by unevenly applying fertiliser to the moso bamboo stand [ 14 ]; this is due to the special “rhizome–culm” system of bamboo, a typical clone of the plant, which makes the whole bamboo stand connected like multiple branches of a tree [ 15 ]. Nutrients integrated physiologically in the rhizomes are transported to the ramets together with water, affected by branching and the environment [ 16 , 17 , 18 , 19 , 20 ]. The direction of transport of substances in rhizomes is bidirectional and related to source–sink relationships, either along the rhizomes or going through rhizomes, so that parent bamboos of every age may provide nutrients for bamboo shoots [ 17 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients integrated physiologically in the rhizomes are transported to the ramets together with water, affected by branching and the environment [ 16 , 17 , 18 , 19 , 20 ]. The direction of transport of substances in rhizomes is bidirectional and related to source–sink relationships, either along the rhizomes or going through rhizomes, so that parent bamboos of every age may provide nutrients for bamboo shoots [ 17 , 21 , 22 ]. The source of nutrients in bamboo shoots during such rapid growth remains unknown until the influence of different age parent culms is clarified.…”
Section: Introductionmentioning
confidence: 99%